Seismic Imaging of the Westward Transition From Yakutat to Pacific Subduction in Southern Alaska - Florian Millet; Stéphane Rondenay; Thomas Bodin; Carl Tape (Geochemistry, Geophysics, Geosystems, 2023)
Abstract Alaska is located at the northernmost point of the interface between the Pacific plate and the North American continent. The subduction of the Pacific plate generates arc volcanoes along the Aleutian trench, which stops to the east at the Denali Volcanic Gap. This volcanic gap has been linked to the underthrusting of the Yakutat terrane, which might alter the thermal state of the mantle wedge and prevent melt formation. This implies that the limits of the volcanic activity should mirror the extent of the Yakutat subduction. However, the transition from the Pacific slab to the Yakutat terrane at depth is not fully understood. To investigate this issue, we processed a new composite seismic data set from six arrays deployed in the region from 2000 to 2018. We apply a multi‐mode 3D Kirchhoff migration to obtain high‐resolution 3D scattering images of the region. Our results highlight a sharp lateral boundary in the slab structure, with a 10 km Moho step, just offshore Anchorage, and a more gradual slab transition beneath the southern part of the Kenai peninsula. Our images from the Yakutat slab plunge down to 150 km depth are consistent with previous estimates of the Yakutat slab extent below the Alaska Range. Although the steeply dipping boundaries of the subducting Pacific lithospheres are not fully recovered, deep coherent signals from the Pacific slab are observed down to 150 km depth. These observations suggest that the crust is still partially uneclogitized at these depths in both slabs.